CREATION AND STANDARDIZATION OF “THE INTERSUBJECTNESS DIAGNOSTIC SURVEY” - Nakonechna, Maria (PSYCHOLOGICAL JOURNAL, 2019)
Intersubjectness concept includes such features of human co-operation, which are focused on unleashing the potential of a person, improvement of personal subjectness, balance of empathy and self-realization in communication. The article proves that intersubjectness is closely related with activity, creativity, responsibility and reflexivity and thus, actually, happens to be a projection of self-actualization idea (A. Maslow) on the plane of interpersonality relations. The process of creation and standardization of Intersubjectness Diagnostic Survey lasted from August 2017 to February 2019, including pilot research and basic empiric research; results of the latter are presented in this article. 518 Ukrainian-speaking persons of young age with different residences and places of study (Nizhyn, Kyiv, Sumy, Chernihiv, Snovs’k, Pakul’) formed the test sample. Cronbach's alpha for the sample α=0,831, that is quite good level (higher than 0,8) of internal co-ordination and reliability of the survey. Survey showed sufficient retest reliability (Spearman's rank correlation coefficient r=0,516, р≤0,01) among test values of high school students at 6-months intervals between psychodiagnostic cross sections. Through Student's t-distribution statistically meaningful difference in intersubjectness was revealed between groups of men and women, diagnosed by means of Intersubjectness Diagnostic Survey. To check survey’s validity, results were compared with values received using alternative methods, such as vitality test (E.M.Osin screening version), scale of general efficiency, test of life-meaning orientations, «Level of subjective control» questionnaire, questionnaire of reflectivity by A.V. Karpov, questionnaire of emotional empathy. Substantial cross-correlations with all scales and methods, which were compared with Intersubjectness Diagnostic Survey, proves constructive and convergent valifity of this psychodiagnostic tool. Following factors were distinguished as the result of factor analysis: «Understanding of people and personal inspiration»; «Communication and co-operation»; «Accounting of other’s subject position»; «To hear other person and to be heard». Test norms were distinguished by means of z-scores with further calculation of low, middle and high levels of intersubjectness. The aim, research subject and field application of Intersubjectness Diagnostic Survey (by M. M. Nakonechna) are specified as well as detailed instruction to the questionnaire, its text and points calculation method.